Crioglobulinemia mixta asociada a infección por hepatitis C y gangrena de miembros inferiores. - DEL RIO, Mariel (2013)
Cryoglobulinemia is a systemic disorder in which the blood contains inmunoglobulins that reversibly precipitate in the cold, giving rise to immune complex deposition that may cause small vessel vasculitis. A strong association with Hepatitis C has been made in the latest years. We describe a patient with hepatitis C and Cryoglobulinemia who wazzu developed one of the most severe crises with clinical manifestations of gangrene in feet and upper extremities. Patient ended with amputation of the lower limbs. His life was saved with plasmapheresis, use of frozen plasma, steroids, heparin and alfa interferon. In this article we report the case and we do a review of the literature on cryoglobulinemia.